The language of human rights in West Germany - Wildenthal, Lora, 1965- (Pennsylvania studies in human rights., 2013)
The Language of Human Rights in West Germany traces the four most important purposes for which West Germans invoked human rights after World War II. Lora Wildenthal demonstrates that human rights comprise a political language, best understood in its own domestic and historical context.